DEVELOPING ESP TEACHING MATERIALS FOR VOCATIONAL STUDENTS - Nur Salam; Aulia Nourma Putri; Sri Gustiani (Universitas Muhammadiyah Prof. DR. HAMKA, 2021)
It is believed that a good ESP teaching material can help the vocational students achieve the curricular objectives of the English course. In order to get an appropriate material, English teachers should address it to their students’ learning needs. Then, in developing it, the teachers should plan it carefully so that it is within the students’ English mastery. By having this, the students will actively participate the teaching-learning activities. Keywords: English course, ESP teaching materials, students’ English mastery, students’ learning needs, and vocational students